Intraoperative Dexamethasone Implant in Uveitis Patients with Cataract Undergoing Phacoemulsification. (13th August 2013) - Gupta, Adit; Ram, Jagat; Gupta, Amod; Gupta, Vishali
Abstract: Purpose : To study the role of intraoperative intravitreal dexamethasone implant in patients of uveitis with cataract undergoing phacoemulsification. Methods : This prospective study included 20 patients with uveitis and cataract who underwent phacoemulsification with intraocular lens implantation. Ten patients (10 eyes) received an intravitreal dexamethasone implant intraoperatively (implant group), and 10 patients (10 eyes) received oral steroids (steroid group). Outcome measures were best-corrected visual acuity (BCVA), intraocular pressure (IOP), and central macular thickness (CMT). Results : The logMar BCVA improved from 0.93 ± 0.49 to 0.23 ± 0.23 and from 1.29 ± 0.47 to 0.22 ± 0.16 in the implant and steroid groups, respectively. Postoperative IOP and CMT showed no statistically significant differences between the two groups. None of the patients in either group had significant IOP rise requiring any surgical intervention. Conclusions : A single intraoperative intravitreal dexamethasone implant during phacoemulsification in patients of uveitis with cataract seems to be an effective alternative for postoperative oral steroids.